Pancreaticoduodenal Artery Aneurysm Formation with Superior Mesenteric Artery Stenosis - Kitaoka, Tadashi (The Editorial Committee of Annals of Vascular Diseases, 2014)
Celiac stenosis or occlusion is attributed partly to increase blood flow at pancreatic arcade from the superior mesenteric artery (SMA) system and may play a causal role in true aneurysm of pancreaticoduodenal artery (PDAA) formation. However, despite possible increased blood flow in the pancreatic arcades like celiac stenosis, PDAAs with a stenotic SMA are extremely rare, with only three cases have been reported in the literature. We report a case of PDAA with SMA stenosis and review the literature.